2021
DOI: 10.1177/10690727211005653
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Perceived Future Decent Work Securement Among Chinese Impoverished College Students

Abstract: Drawing from Psychology of Working Theory (PWT), the current study sampled 254 college students from impoverished families in China and examined their perceptions of access to future decent work as predicted by subjective social status and marginalization and mediated by work volition and career adaptability. As impoverished college students are socioeconomically disadvantaged and thus cannot afford college expenses, understanding their perception regarding future careers echoes the call for renewing the focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 63 publications
3
31
1
Order By: Relevance
“…Indeed, the PWT is an inclusive theory that embraces everyone who works and wants to work worldwide and is appropriate for individualistic and collectivist cultures (Blustein, 2013;Duffy et al, 2019). Several studies have explored the global applicability of the PWT, including applicability in Eastern countries and collectivist cultures, such as Turkey (Kozan et al, 2019), South Korea (Kim et al, 2019;Kim et al, 2020), and China (Wang et al, 2019;Wei et al, 2021). Recently, Chinese researchers have begun to clarify how the PWT is understood in contemporary China.…”
Section: The Psychology Of Working Theory and Work Need Satisfaction In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the PWT is an inclusive theory that embraces everyone who works and wants to work worldwide and is appropriate for individualistic and collectivist cultures (Blustein, 2013;Duffy et al, 2019). Several studies have explored the global applicability of the PWT, including applicability in Eastern countries and collectivist cultures, such as Turkey (Kozan et al, 2019), South Korea (Kim et al, 2019;Kim et al, 2020), and China (Wang et al, 2019;Wei et al, 2021). Recently, Chinese researchers have begun to clarify how the PWT is understood in contemporary China.…”
Section: The Psychology Of Working Theory and Work Need Satisfaction In Chinamentioning
confidence: 99%
“…Wang et al (2019) demonstrated the significant mediating roles of work volition and access to decent work in the relationship between social status and career-related outcomes among Chinese urban workers. Wei et al (2021) examined how contextual factors influenced Chinese college students' perceptions and how, constrained by their backgrounds, impoverished college students may have limited financial and social resources to act volitionally when making career choices after graduation.…”
Section: The Psychology Of Working Theory and Work Need Satisfaction In Chinamentioning
confidence: 99%
“…Furthermore, mobility derived from a market-oriented economy and urbanization has greatly challenged the basis of the traditional hukou registration system and forced the government to adjust its policies, including allowing migrants to change their hukou category after they have been employed in a city for a certain period (Chan and Zhang, 1999 ; Lu and Wan, 2014 ). Thus, mobility constraints (Wei et al, 2022 ) have been taken seriously and largely resolved. Therefore, the finding that hukou does not have a negative impact of classism on work volition is understandable (e.g., Wang et al, 2019 ; Kim and Allan, 2021 ), based on the analysis above.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, college students are likely at critical points in their decision-making process (Duffy et al, 2016b ), and making a career decision is an important career issue for them (Cheung et al, 2020 ). On the other hand, college students are likely to face increasing barriers to achieving their ultimate career goals (Duffy et al, 2012 ; Cheung et al, 2020 ), such as mobility constraints (Wei et al, 2022 ), although they are considered at the top of the career privilege pyramid and possess more freedom and volition than others when making their career choice because of professional competence, qualifications, and generic skill sets (e.g., analytical skills and critical thinking) based on on-campus training and exposure to extracurricular programs (Cheung et al, 2020 ). Therefore, it is necessary to examine the state of the population; however, previous studies have been largely restricted to working adults (Wei et al, 2022 ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Fourth, the decent work concept differs from other concepts such as quality of working life, as it is also characterized by a future perspective (Brill, 2021). That is also the reason why decent work is suggested to be regarded as aspired dimensions of work rather than as immediately achievable goals (Webster et al, 2015). How people make sense of their work-related aspirations in their specific contexts is perceived to influence their present and future wellbeing .…”
Section: Introductionmentioning
confidence: 99%